Sign Language in Action - Napier, Jemina; Leeson, Lorraine; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
This book defines the notion of applied sign linguistics by drawing on data from projects that have explored sign language in action in various domains. The book gives professionals working with sign languages, signed language teachers and students, research students and their supervisors, authoritative access to current ideas and practice.
Keywords: Sign language; Language and languages-Study and; Sociolinguistics; Literature-Translations.; Translating and interpreting